Seven wonders of the industrial world - Britsh Broadcasting Company (BBC). (London BBC, 2004)
Seven Wonders of the Industrial World uses a compelling mix of computer-generated and dramatic recreations to bring these fascinating stories to life.
"Meet the most brilliant pioneers of the industrial age, and their most remarkable feats of engineering. See how, against all odds, their burning ambitions, extravagant dreams, passion and rivalry produced seven key technological monuments of the Industrial Revolution."--Container.
1. The great ship -- 2. The Brooklyn bridge -- 3. Bell rock lighthouse -- 4. The Sewer king -- 5. The Panama canal -- 6. The line -- 7. The Hoover dam.
Library has: VDR-1590-1591 (2 DVDs)
Series producer, Deborah Cadbury ; executive producer, Jull Fullerton Smith ; narrated by Robert Lindsay.
DVD videos
Keywords: Bell Rock Lighthouse (Scotland); Brooklyn Bridge (New York, N.Y.); Hoover Dam (Arizona and Nevada); Panama Canal (Panama); Railroads -- United States; Sewerage -- England; Technological innovations -- History